Exploring reflective journal writing among pre-registered student nurses / Fatemeh Seyed Abolghasem - Fatemeh , Seyed Abolghasem (2020)
This study furnishes a comprehensive exploration of reflective journal writing in diploma nursing education of pre-registered student nurses (PRSN) in a Malaysian context. The focal point is directed toward the practice of reflective journal writing and the roles it plays in developing professional knowledge and skills among novice student nurses. Within this domain, this study explored the participants’ perceptions on reflective journal writing, investigated their evaluation of reflective journaling and looked into their levels of reflection demonstrated in their reflective journals as documented in Transformative Learning Theory (TLT) proposed by Mezirow (1990). For these purposes, dual methodologies were adopted to answer the research questions. Initially, the quantitative descriptive method was implemented for data collection and analysis utilizing a structured survey questionnaire to thirty PRSN to explore their perceptions on reflective journaling. In order to contribute more scientific results, Importance-Performance Analysis Matrix (IPA) proposed by Martilla and James (1977) was employed; the results showed that the participants required more comprehensive orientation about the importance of reflective journaling in nursing education. Furthermore, the qualitative case study was conducted to explore the levels of reflection revealed in the reflective journals and the verbatim of focused and one-to-one interviews. These documents were analyzed deductively and inductively utilizing the concepts of three levels of reflection from the heart of TLT. Based on the findings, the study discussed that almost all participants were positive about reflective journaling in the process of learning. They also acknowledged reflective journaling could enhance their learning at micro level, the self-directed learning as the main capital of reflective journaling, increase their ability at meso and macro levels, the ability to appreciate collaborative learning and communication with more knowledgeable ones in and out of clinical posting. Moreover, through the lens of TLT, the results showed that from the time the student nurses get involved with nursing practice, and start to practice in authentic situation, they demonstrate their ability of reflection in three levels of content (what), process (how), and premise (why) not in a linear but in cyclical fashion which they are overlapping as well. This study concluded that grouping the student nurses as non-reflector, reflector, or critical reflector seems inadequate since they were involved in reflection of any forms from the initial stage of working in the practicum. Based on the findings, this can be discussed as the theoretical implication to the body of knowledge. The findings have significant implications for nursing education. That is, prominently incorporated reflective journal writing into the nursing curriculum can be considered as a strategy to improve nursing students’ experiential and practical knowledge that assists them in the journey of becoming professional. Being critical and having the ability to reflect at higher order of thinking is a valuable asset that can allow learners to salvage learning that stay with them all through their lives. However, being critical is not a common practice in Malaysian culture. Thus, the future research could accommodate culture-fraught nature of critical thinking in reflective journaling a leading approach in pedagogy.